CONSUMER BEHAVIOR PREDICTION ANALYSIS BASED ON RATIONALISM AND UNDERSTANDING ABOUT CONSEQUENCES TOWARDS PIRATED DIGITAL PRODUCTS - Palus, Palus; Haryanto, Jony Oktavian (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2016)
This research is conducted to examine consumer perception related with rationalization and understanding of risk consequences and their advantages by predicting desires related with digital product piracy. The motivation to conduct digital piracy is reinforced with understanding the advantages obtained and consumer behavior towards digital product piracy. Various rationalization techniques also support reinforcing their motivation to engage in piracy. Interestingly, that motivation can be hindered with perceptions about the consequences or social norm regulations and moral responsibilities. Analytical results reveal that consumer intention to use pirated digital products can continuously increase, because it is influenced by the understanding of the advantages obtained, the rational techniques used, their attitudes toward piracy, and perceptions in controlling behavior. On another side, moral responsibilities and social norms also play a role in reducing the intensity of using pirated digital products.